Emerging microalgae-based biofuels: Technology, life-cycle and scale-up. (June 2023) - Marangon, B.B.; Magalhães, I.B.; Pereira, A.S.A.P.; Silva, T.A.; Gama, R.C.N.; Ferreira, J.; Castro, J.S.; Assis, L.R.; Lorentz, J.F.; Calijuri, M.L.
Abstract: Microalgae biomass is a versatile feedstock with a variable composition that can be submitted to several conversion routes. Considering the increasing energy demand and the context of third-generation biofuels, algae can fulfill the increasing global demand for energy with the additional benefit of environmental impact mitigation. While biodiesel and biogas are widely consolidated and reviewed, emerging algal-based biofuels such as biohydrogen, biokerosene, and biomethane are cutting-edge technologies in earlier stages of development. In this context, the present study covers their theoretical and practical conversion technologies, environmental hotspots, and cost-effectiveness. Scaling-up considerations are also addressed, mainly through Life Cycle Assessment results and interpretation. Discussions on the current literature for each biofuel directs researchers towards challenges such as optimized pretreatment methods for biohydrogen and optimized catalyst for biokerosene, besides encouraging pilot and industrial scale studies for all biofuels. While presenting studies for larger scales, biomethane still needs continuous operation results to consolidate the technology further. Additionally, environmental improvements on all three routes are discussed in light of life-cycle models, highlighting the ample research opportunities on wastewater-grown microalgae biomass. Graphical abstract: Image 1 Highlights: Biohydrogen, biokerosene and biomethane are identified as emerging algal biofuels. Theoretical and practical biomass conversion aspects are presented for each route. Sustainable use of wastewater-based algal systems is encouraged. Feasible up-scaled production depends on improved biomass growth rates.